مدى توافر عناصر الهوية الوطنية في الكتب المدرسية لمناهج التاريخ في مرحلة التعليم المتوسط. - رابحي, اسماعيل (Sciences de l'Homme et de la Société, 2013)
هدف الإصلاح التربوي للمنظومة التربوية إلى ترسيخ عناصر الهوية الوطنية لدى الناشئة وذلك من خلال إعادة تنظيم المحتويات التربوية للمناهج التعليمية المدرسة، ومنها مناهج التاريخ والتي تعد من أهم المداخل المعرفية التي تسهم في تنمية الانتماء الوطني للتلاميذ. وعليه نحاول في هذه الدراسة الكشف عن مدى توافر أبعاد الهوية الوطنية في الكتب المدرسية لمناهج التاريخ في مرحلة التعليم المتوسط.     The reform of the educational system aimed at emphasizing the elements of the national identity, through the reorganization of educational contents of the taught school curricula, among which the curriculum of history, which is one of the main entrances of knowledge that contribute to the development of national belonging for pupils. Therefore, we try, in this study, to detect to what extent the dimensions of national identity are available in school textbooks of history in the curricula of middle school education